Draft Annual Plan 1988-89 Government of Bihar - Planning Commission (Planning Commission, 1988)
The incidence of poverty has also declined in the State. The percentage of the people below the poverty line in Bihar has declined from 57.5 in 1977-78 to 49.5 in 1983-84. During the same period, the percentage of the people below the poverty line in the country declined from 48.1 to 37.1 Although Bihar has recorded a fall in the percentage of the people below the poverty line, it has the highest poverty percentage in the country. Performative of The Seventh Five-Year Plan. The State Government bad proposed a Draft Seventh Plan of Rs. 7002 crores which was quite modest and based on anticipated resources taking into account the recommendations of the Eighth Finance Commission.
Planning Department